Srovnání měření tloušťky a zakřivení rohovky pomocí Scheimpflugovy kamery, laserové interferometrie, automatické keratometrie a ultrazvukové pachymetrie - Pašová, P; Skorkovská, K; Michálek, J (Ceska a slovenska oftalmologie, 2012)
INTRODUCTION: The aim of our study was to compare keratometry and central corneal thickness measurements obtained with three different ophthalmic devices and to decide if they can be used interchangeably in clinical practice. METHODS: 43 healthy persons were included in the study (29 women and 14 men, average age 25 ± 3.5 years). Central corneal thickness (CCT) was measured with the Scheimpflug HR imaging system (Pentacam), Allegro BioGraph and with ultrasound pachymetry (RXP OcuScan). Keratometry in two main meridians of the cornea (K1, K2) was measured with Pentacam, Allegro BioGraph and automated keratometry. RESULTS: The mean difference in K1-readings was 0.01 ± 0.31 D for BioGraph vs. automated keratometry, 0.06 ± 0.23 D for BioGraph vs. Pentacam and 0.05 ± 0.34 D for automated keratometry and Pentacam. The mean difference in K2-readings was 0.29 ± 0.45 D for BioGraph vs. automated keratometry, 0.11 ± 0.28 D for BioGraph vs. Pentacam and 0.19 ± 0.44 D for automated keratometry and Pentacam. The interdevice differences were in all cases statistically significant (p < 0.05). The mean difference in CCT was 4.57 ± 7.84 μm for BioGraph vs. ultrasound, 4.33 ± 7.55 μm for BioGraph vs. Pentacam and 8.90 ± 7.49 μm for ultrasound vs. Pentacam. The interdevice differences in CCT were also statistically significant (p < 0.05). CONCLUSION: Our results suggest that the measurements of keratometry and CCT may differ significantly between the tested machines and therefore should not be used interchangeably in clinical practice.
Keywords: interferometrie; fotografování; pachymetrie rohovky; rohovka; mužské pohlaví; Corneal Topography; Adult; Interferometry; Corneal Pachymetry; ultrasonografie; ženské pohlaví; Humans; Ultrasonography; rohovková topografie; dospělí; Female; Cornea; lidé; Male; Photography